2016
DOI: 10.1128/jvi.02400-15
|View full text |Cite
|
Sign up to set email alerts
|

Functional Genomics Reveals Linkers Critical for Influenza Virus Polymerase

Abstract: Influenza virus mRNA synthesis by the RNA-dependent RNA polymerase involves binding and cleavage of capped cellular mRNA by the PB2 and PA subunits, respectively, and extension of viral mRNA by PB1. However, the mechanism for such a dynamic process is unclear. Using high-throughput mutagenesis and sequencing analysis, we have not only generated a comprehensive functional map for the microdomains of individual subunits but also have revealed the PA linker to be critical for polymerase activity. This PA linker b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 36 publications
(48 reference statements)
0
16
0
Order By: Relevance
“…(C) The specific recognition of the serum used was tested against whole infected-cell extracts by Western blotting. pA104R-DNA interactions were not detected under high-ionic-strength conditions (Ն2 M NaCl), indicating that pA104R-binding activity involves ion pair formation, as reported for other viral DNA-binding proteins (26)(27)(28).…”
Section: Figmentioning
confidence: 57%
“…(C) The specific recognition of the serum used was tested against whole infected-cell extracts by Western blotting. pA104R-DNA interactions were not detected under high-ionic-strength conditions (Ն2 M NaCl), indicating that pA104R-binding activity involves ion pair formation, as reported for other viral DNA-binding proteins (26)(27)(28).…”
Section: Figmentioning
confidence: 57%
“…Genome-wide mutational analysis, has shown that IAV cannot tolerate substitutions in these motifs 46 . More interesting, however, is the IBV-wide cross-reactivity conferred by the BHA 543 peptide.…”
Section: Discussionmentioning
confidence: 99%
“…the universal A2/PB1 413 and two IBV-specific (A2/BHA 543-551 and A2/NS1 266-274 hereafter A2/BHA 543 and A2/BNS1 266 ) epitopes. To further understand the role of the universal A2/PB1 413 + CD8 + T cells in the immunodominance hierarchy following either IAV or IBV infection, we established IAV-or IBV-specific CD8 + T cell lines in vitro from PBMC of healthy adults (n=11) and assessed tetramer-specific CD8 + T cell responses against IAV epitopes (A2/M1 58-66 (A2/M1 58 ) , A2/PA [46][47][48][49][50][51][52][53][54] (A2/PA 64 ) , A2/PB1 413 ) and IBV epitopes (A2/BHA 543 , A2/BNS1 266 , A2/PB1 413 ). Consistent with our IFNγ staining ( Fig.…”
Section: Immunodominance Of Universal A2/pb1 413 + Over Ibv-specificmentioning
confidence: 99%
“…Regarding the highly pathogenic nature of HE144 in Pekin duck, several amino acid differences in PB2, PB1, PA and HA were observed when we compared the genome of HE144 with the consensus sequences of the other viruses we studied. One of these differences was at the PA‐arch domain of PA that binds to vRNA (Wang et al., ). A H5N1 HPAIV possessing D383 in the PA‐arch domain of PA killed ducks and D383 in PA affected polymerase activity and decreased the accumulation of PA in the nucleus (Song et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the highly pathogenic nature of HE144 in Pekin duck, several amino acid differences in PB2, PB1, PA and HA were observed when we compared the genome of HE144 with the consensus sequences of the other viruses we studied. One of these differences was at the PA-arch domain of PA that binds to vRNA (Wang et al, 2015).…”
Section: Discussionmentioning
confidence: 99%